INDONESIA SEBAGAI TRENDSETTER MODERATISME DI ASEAN (Membangun Relasi Akademik antara Islam dan Multikulturalisme) - Winarto Eka Wahyudi (Universitas Islam Lamongan, 2019)
Indonesia is the largest Muslim majority country in the world. So it makes perfect sense if Islam in Indonesia becomes the centre of civilization on the international scene. However, this achievement is not easy because it demands moral responsibility that Islam indeed shows its moderate and tolerant face. Why is this important? Because the entire Islamic region in the Middle East country, only shows Islam in front of conflict and war. So, the claim that the future of Islamic civilization in the world is in the hands of Indonesia is not a mere figment. For this reason, Indonesian Islam must be able to maintain and simultaneously make efforts to support the preservation of Islam that is friendly to all elements of the nation. For this reason, in this paper, the author describes how strategies so that Islam can become a value base to give birth to attitudes of moderates in the frame of Multicultural Islamic education.